Adsorption of Antimony by Bagasse Fly Ash Chemical Modification and Adsorption Mechanism - Leechart, Piyawan (Water environment research : a research publication of the Water Environment Federation, 2016)
Modification of bagasse fly ash (BFA) and the adsorption mechanism of antimony (Sb) by modified BFA were studied. It was found that BFA grafted with acrylic acid (BFAG) and BFA treated with hydrochloric acid (BFA/HCl) led to a decrease in the pH of the zero point of charge (pHzpc) of the adsorbents. The pHzpc of BFA, BFAG, BFA/HCl and activated carbon (AC) were 8.3, 6.4, 6.2 and 8.2, respectively. The maximum adsorption capacities (Qmax) of Sb by BFA, BFAG, BFA/HCl and AC were 0.14, 0.34, 0.38 and 0.29 mg Sb/g adsorbent, respectively. Modified BFA had Qmax higher than AC although the BET surface area of AC was the highest. This was due to the system pH of BFAG and BFA/HCl was 5.20-6.00 and the pHzpc of BFAG and BFA/HCl accounted for 6.4 and 6.2, respectively. Therefore, the adsorbent surface had a positive charge, resulting in increasing adsorption of Sb